Hukuman Kebiri Kimia Bagi Pelaku Kekerasan Seksual Terhadap Anak Perspektif Fiqh Siyasah - Lukman Arake (Al-Adalah: Jurnal Hukum dan Politik Islam, 2020)
Responding to the high number of sexual violence against children, President Jokowi enacted the Regulation of Child Protection which in regulated chemical castration punishment as an additional penalty for perpetrators of sexual violence. However, a few years after the enactment, case of sexual violence against children remained high, but in fact there were no perpetrators of sexual violence that were castrated with chemicals. Because, the competence to do the castration chemistry  by profession of doctor, but the Indonesian Doctors Association (IDI) refused to become the executor of castration chemistry, for reason of  a humanity and violate a medical oath. Based on it, a chemical castration  need to be explored in the perspective of Fiqh Siyasah. This research is a socioyuridical study, which relies on qualitative data, so to describe the castration  punishment in Siyasah Fiqh perspective, the author used two approaches, that was  the statutory approach and conceptual approach. The result of the research show that, normalizing chemical castration as an additional type of penalty for perpetrators of sexual violence is based on the consideration that (i) sexual violence against children is a very dangerous crime because this crime did not appear to the surface, (ii) made many victims accompanied with a long trauma, (iii) can even encourage victims to do suicide. (iv) In another, the perpetrators were not only Indonesian citizen, but foreigner who came to Indonesia in the guise of tourists and had a desire to look for a victim. However, out of these consideration, in the perspective of fiqh siyasah, based on the agreement of the cleric the application of chemical castration to perpetrator of sexual violence is unlawful. But the perpetrator can be convited to death, if the act is done repeatedly.